The Genetics of Aortopathies in Clinical Cardiology. Issue 11 (24th May 2017) - Goyal, Amit; Keramati, Ali R; Czarny, Matthew J; Resar, Jon R; Mani, Arya
Aortopathies pose a significant healthcare burden due to excess early mortality, increasing incidence, and underdiagnosis. Understanding the underlying genetic causes, early diagnosis, timely surveillance, prophylactic repair, and family screening are keys to addressing these diseases. Next-generation sequencing continues to expand our understanding of the genetic causes of heritable aortopathies, rapidly clarifying their underlying molecular pathophysiology and suggesting new potential therapeutic targets. This review will summarize the pathogenetic mechanisms and management of heritable genetic aortopathies with attention to specific forms of both syndromic and nonsyndromic disorders, including Marfan syndrome, Loeys-Dietz syndrome, vascular Ehlers-Danlos syndrome, and familial thoracic aortic aneurysm and dissection.